>1200 V GaN‐on‐silicon Schottky diode. Issue 5 (27th March 2013) - Boles, T.; Varmazis, C.; Carlson, D.; Palacios, T.; Turner, G. W.; Molnar, R. J.; Krishna, Sanjay; Plis, Elena
Abstract M/A‐COM Technology Solutions has continuing joint development efforts sponsored by the Department of Energy with MIT main campus and MIT Lincoln Laboratory to develop GaN on silicon two and three terminal high voltage/high current switching devices. The initial developmental goals were for a Schottky diode that has a reverse breakdown blocking voltage of >600 V and is capable of handling 10 A of forward current. A comparison of the M/A‐COM Technology Solutions lateral GaN Schottky diode on‐resistance as a function of reverse breakdown voltage for a number of both lateral and vertical GaN Schottky diode geometries taken from the literature is presented. The substrates employed for all of these data points are either sapphire, SiC, silicon, and even one study which utilized single crystal GaN. Also included in this plot are theoretical limits for the basic materials typically used in GaN Schottky diode construction. It can be seen that the reverse breakdown results of approximately 1500 V for M/A‐COM Technology Solutions lateral anode connected field GaN Schottky diodes on silicon substrates compare extremely favorably with the reported performance of the state‐of‐the‐art devices, regardless of substrate material or design geometry. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)